Altered retinal oxygen metabolism in patients with combined ocular and central nervous system sarcoidosis. (13th December 2020) - Kindt, Astrid; Byg, Keld-Erik; Wied, Jimmi; Ellingsen, Torkell; Davidsen, Jesper Rømhild; Grauslund, Jakob
Abstract: Objective: To evaluate retinal oxygen metabolism by retinal oximetry for ocular and CNS diseases in a cross-sectional study of sarcoidosis. Methods: Overall 201 eyes from 103 biopsy-verified sarcoidosis patients were included and divided into four groups depending on the organ affection: (i) sarcoidosis without ocular or CNS affection, (ii) ocular sarcoidosis, (iii) CNS sarcoidosis, and (iv) combined ocular and CNS sarcoidosis. Retinal oximetry was obtained and analysed, with the mean retinal arteriolar and venular saturation as well as arteriovenous difference as principal outcomes. Comparison between groups was done in a multi linear regression model adjusted for age, sex, duration of sarcoidosis, best corrected visual acuity and retinal oximetry quality. Results: Mean (s .d .) age was 50.5 (13.4) (95% CI: 47.9, 53.1) years and 52.2% were males. Eyes of the combined Ocular/CNS group had a higher retinal arteriovenous difference than eyes of the Non-ocular/no-CNS group (42.1% vs 37.7%, P  = 0.012) but did not differ between other groups. Eyes in the four groups (Non-ocular/no-CNS, Ocular, CNS and Ocular/CNS) did not differ according to retinal arterial (94.5%, 93.5%, 93.5% and 94.5%, respectively) or venular (57.5%, 56.4%, 55.0% and 52.5%, respectively) oxygen saturation. Conclusions: The results of this study suggest that eyes of sarcoidosis patients with combined ocular and CNS affection have an altered oxygen metabolism indicating a subclinical eye affection that is not recognized by conventional screening methods.